Peningkatan Pembelajaran Tematik Terpadu dengan Menggunakan Model Quantum Teaching di Sekolah Dasar - Dewi, Dini Putri Pratama; Miaz, Yalvema (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This study aims to describe an increase in student learning outcomes in integrated thematic learning using the Quantum Teaching model. This type of research is conducted in the second semester of the 2018/2019 academic year. The subject of the research is teachers and students, the number of students is 16 people. The research data is obtained from observation and evaluation. Research procedures are planning, implementation, observation, and reflection. The research results from planning cycle I average value 80.5% qualification B, Cycle II average value 92% qualification A.Teacher aspects cycle I average value 83% qualification B, siklua II average value 100% qualification A.Student aspects of cycle I average value 83% qualification B, cycle II average 100% qualification A Learning outcomes cycle I average value 78.5% criterion C, cycle II average value 91% criteria A. It was concluded that the Quantum Teaching model can improve student learning outcomes.